Changes of Plant Necro Mass and Soil Faunal Composition in Wetlands Caused by Conversion of Forest to Oil Palm Plantation (Journal of Wetlands Environmental Management, 2024)
Field research was carried out to elucidate the trajectories of the temporal changes in vegetation and soil faunal diversities in wetlands caused by conversion of forests to oil palm plantations. Soil blocks sizing 30 cm x 30 cm x 30 cm were evacuated from three oil palm fields with three different ages (i.e., 2 years, 6 years, and 10 years old), as well as in secondary forest on peat soils. Fauna found in the blocks were subjected to 70 % ethanol sterilization before hand sorter and identification. The diversity index of earthworm was calculated based on the Shannon-Wiener formula. Quadrats were employed to determine the plant structure (i.e., species abundance). A t-test was employed to assess the differences between treatments. The results showed that the ages of the oil palm cultivation affected vegetation and soil faunal structures. The diversity indexes of earthworm were 0.12, 2.49, 1.77, and 1.73 in secondary forest, 2, 6, and 10 years-old oil palm fields, respectively. Similar trends occurred on diversity of Imperata cylindrica. These findings suggested that the diversities of Imperata cylindrica and soil fauna in wetlands in the tropics increased at early development of oil palm development and decreased onwards.